The Limits of Art On Borderline Cases of Artworks and their Aesthetic Properties - Benovsky, Jiri (SpringerBriefs in Philosophy,, 2021)
This open access book is about exploring interesting borderline cases of art. It discusses the cases of gustatory and olfactory artworks (focusing on food), proprioceptive artworks (dance, martial arts, and rock climbing qua proprioceptive experiences), intellectual artworks (philosophical and scientific theories), as well as the vague limits between painting and photography. The book focuses on the author's research about what counts as art and what does not, as well as on the nature of these limits. Overall, the author defends a very inclusive view, 'extending' the limits of art, and he argues for its virtues. Some of the limits discussed concern our senses (our different perceptual modalities), some concern vagueness and fuzzy boundaries between different types of works of art, some concern the amount of human intention and intervention in the process of creation of an artwork, and some concern the border between art and science. In these various ways, by understanding better such borderline cases, Benovsky suggests that we get a better grip on an understanding of the nature of art.